The Evolution and Synthesis of the Concept of Death Between the Old Testament and the New Testament - WANG, Zhijun (Journal of Research for Christianity in China (JRCC), 2025)
There is no consistent understanding the concept of death throughout The Bible. In the attitude of life and the concept of death, there are many contradictions between the Old and New Testament. The fact that Jesus was Christ and died and was resurrected transmutes the concept of death. Christians have raised hopes of resurrection and eternal life through faith in Jesus, who rose from the dead. In the encounter with the death of Jesus, the concept of death in the Old Testament changes and synthesizes.
Keywords: The Bible, Old Testament, New Testament, Faith, The Concept of Death